Islamic theology and philosophy : studies in honor of George F. Hourani - Hourani, George Fadlo; Marmura, Michael E., 1929- (State University of New York Press, 1984)
English and French. Includes bibliographical references and index.
English and French.
Keywords: Hourani, George Fadlo.; Hourani, George Fadlo; Islamic philosophy.; Islam -- Doctrines.; Philosophie islamique.; BIOGRAPHY & AUTOBIOGRAPHY -- General.; PHILOSOPHY -- Eastern.; Islam -- Doctrines; Islamic philosophy; Islamische Theologie; Aufsatzsammlung; Islamische Philosophie; Bibliografie; Islamitische filosofie.; Islam.; Essays.